Impact of Structural Funds and Cohesion Fund for Regional Development in Poland - Dudzik, Konrad; Głowacki, Jakub (Journal of Public Governance, 2010)
The end of 2008, according to the n+2 rule, ended in Poland the implementation of projects in the programming period 2004-2006. This is time to assess the cohesion policy and also estimate the real impact of European funds for socio-economic development. Particularly interesting seems to be conducting such an analysis at the level of voivodeships. To carry it out two methods were used: Perkal method and taxonomic analysis. As a result of the calculations defended the thesis of the positive relation between the value of funds flowing into the region from European funds and the difference in levels of development between 2004 and 2008.